Development of stable self-nanoemulsifying composition and its nanoemulsions for improved oral delivery of non-oncology drugs against hepatic cancer - Onkar B. Patil; Arehalli S. Manjappa; Popat S. Kumbhar; Sourabh P. Bhosale; John I. Disouza; Ahmad Salawi; Unnam Sambamoorthy (Elsevier, 2022)
Cancer remains a major health concern and second leading cause of mortality worldwide. The highest cancer-related mortalities are observed in low and middle-income countries (LMIC) due to unaffordable cost of medicines and lack of safe and effective chemotherapy. Therefore, the key goal of the present research was to develop affordable, safe, efficacious and stable nanoemulsion (NE) system co-loaded with Tadalafil (TDF) and Ketoconazole (KTZ) for repurposing against hepatic cancer. The batch number 1 of SNEDDS was selected as optimized batch based on dispersion time, viscosity and stability. The NE displayed particle size of 41±5 nm (PDI: 0.189±0.064) and Zeta potential of -27.1 mV. The NE exhibited controlled in-vitro release of both TDF (52.37 ± 3.41%) and (KTZ 52.31 ± 3.88%) in PBS pH 6.8 after 24 h. Moreover, the in-vitro hemolysis study showed moderate hemolytic activity of NE towards blood cells. In addition, the in-vitro cytotoxicity study revealed more cytotoxicity of NE than plain TDF and KTZ against HepG2 cell line after 48 h of incubation. Moreover, the HepG2 cellular uptake of TDF and KTZ was found to be substantially higher from NE when compared to the plain TDF and KTZ. Furthermore, NE was found to be stable for more than 6 months with no phase separation and creaming. Stable, safe, effective and affordable NE was developed which might be used as an alternative strategy in the treatment of hepatic cancer and its similar anticancer effect against other cancers need to be validated. Further, TDF and KTZ combination would a potentials approach over approved chemotherapy against hepatic cancer.